CD4+CD56+ natural killer T‐like cells secreting interferon‐γ are associated with incident coronary events. (3rd July 2015) - Björkbacka, H.; Berg, K. E.; Manjer, J.; Engelbertsen, D.; Wigren, M.; Ljungcrantz, I.; Andersson, L.; Hedblad, B.; Fredrikson, G. N.; Nilsson, J.
Abstract: Background: CD3 + CD56 + natural killer T (NKT)‐like cells are a subset of T cells characterized by expression of NK receptors and potent antitumour activity. It has also been suggested that they have a role in autoimmune disease, and levels of NKT‐like cells are elevated in patients with coronary disease. Objectives: To investigate whether high levels of CD3 + CD56 + NKT‐like cells are associated with an increased incidence of cardiovascular disease and a lower incidence of cancer. Methods: This was a prospective study including 700 subjects participating in the baseline investigation of the Malmö Diet and Cancer study between 1991 and 1994. Leucocytes obtained at the baseline investigation and stored at −140 °C were thawed and CD3 + CD56 + cells analysed by flow cytometry. The incidence rates of cancer and coronary events during a mean follow‐up of 15 years were determined through national registers. Results: Subjects in the lowest tertile of interferon (IFN)‐γ‐expressing CD4 + CD56 + cells were found to have an increased risk of incidence of coronary events (log‐rank test: P < 0.05). This association remained significant after controlling for age, sex, smoking, body mass index, hypertension, diabetes and the Th1/Th2 and Th1/Treg cell ratios in a Cox proportional hazards regression model (hazard ratio 1.98, 95% confidence interval 1.24–3.16), but not when the LDL/HDL ratio was included in the model. There were no associations between CD3 + CD56 + NKT‐like cells and incident cancer. Conclusions: The present results could not confirm the hypothesis that low levels of CD3 + CD56 + NKT‐like cells are associated with a higher incidence of cancer and a lower incidence of cardiovascular disease. However, we found that low levels of IFN‐γ‐expressing CD3 + CD4 + CD56 + NKT‐like cells were associated with an increased incidence of coronary events and that this association may be dependent on lipoproteins.